LIQUIDITY AND FINANCIAL DISTRESS IN INDONESIAN TEXTILE AND GARMENT COMPANIES: FIRM SIZE MODERATION - Permana, Dwi; Fadjar, Achmad (Bina Nusantara University, 2025)
This study examines the critical relationship between liquidity and financial distress within Indonesian textile and garment companies listed on the Indonesia Stock Exchange from 2021 to 2023. Faced with recent insolvencies that highlight significant financial struggles in the sector, the research adopted a quantitative methodology, analyzing secondary data from 16 purposively selected firms. The investigation utilized simple linear regression, classical assumption tests for normality, heteroscedasticity, and autocorrelation, and Moderated Regression Analysis to explore the intricate dynamics. A core finding confirms that liquidity has a significant negative impact on financial distress, underscoring that a firm's inability to meet short-term obligations directly escalates its vulnerability to financial hardship. Furthermore, a notable contribution of this study is the identification of firm size as a significant moderator in this relationship. Although larger firms often possess extensive asset bases, they can paradoxically face increased liabilities and risks due to unproductive assets that fail to generate revenue, thereby worsening financial distress. Consequently, the research emphasizes the paramount importance of diligent liquidity management and strategic asset stewardship to ensure the long-term financial viability of these companies. This study offers updated insights into a crucial period and refines the analytical approach by explicitly using the Interest Coverage Ratio (ICR) to measure financial distress.